Siglec-E retards atherosclerosis by inhibiting CD36-mediated foam cell formation - Yaw-Wen Hsu; Fu-Fei Hsu; Ming-Tsai Chiang; Dong-Lin Tsai; Fu-An Li; Takashi Angata; Paul R. Crocker; Lee-Young Chau (Journal of Biomedical Science, 2021)
Abstract Background The accumulation of lipid-laden macrophages, foam cells, within sub-endothelial intima is a key feature of early atherosclerosis. Siglec-E, a mouse orthologue of human Siglec-9, is a sialic acid binding lectin predominantly expressed on the surface of myeloid cells to transduce inhibitory signal via recruitment of SH2-domain containing protein tyrosine phosphatase SHP-1/2 upon binding to its sialoglycan ligands. Whether Siglec-E expression on macrophages impacts foam cell formation and atherosclerosis remains to be established. Methods ApoE-deficient (apoE−/−) and apoE/Siglec-E-double deficient (apoE−/−/Siglec-E−/−) mice were placed on high fat diet for 3 months and their lipid profiles and severities of atherosclerosis were assessed. Modified low-density lipoprotein (LDL) uptake and foam cell formation in wild type (WT) and Siglec-E−/−- peritoneal macrophages were examined in vitro. Potential Siglec-E-interacting proteins were identified by proximity labeling in conjunction with proteomic analysis and confirmed by coimmunoprecipitation experiment. Impacts of Siglec-E expression and cell surface sialic acid status on oxidized LDL uptake and signaling involved were examined by biochemical assays. Results Here we show that genetic deletion of Siglec-E accelerated atherosclerosis without affecting lipid profile in apoE−/− mice. Siglec-E deficiency promotes foam cell formation by enhancing acetylated and oxidized LDL uptake without affecting cholesterol efflux in macrophages in vitro. By performing proximity labeling and proteomic analysis, we identified scavenger receptor CD36 as a cell surface protein interacting with Siglec-E. Further experiments performed in HEK293T cells transiently overexpressing Siglec-E and CD36 and peritoneal macrophages demonstrated that depletion of cell surface sialic acids by treatment with sialyltransferase inhibitor or sialidase did not affect interaction between Siglec-E and CD36 but retarded Siglec-E-mediated inhibition on oxidized LDL uptake. Subsequent experiments revealed that oxidized LDL induced transient Siglec-E tyrosine phosphorylation and recruitment of SHP-1 phosphatase in macrophages. VAV, a downstream effector implicated in CD36-mediated oxidized LDL uptake, was shown to interact with SHP-1 following oxidized LDL treatment. Moreover, oxidized LDL-induced VAV phosphorylation was substantially lower in WT macrophages comparing to Siglec-E−/− counterparts. Conclusions These data support the protective role of Siglec-E in atherosclerosis. Mechanistically, Siglec-E interacts with CD36 to suppress downstream VAV signaling involved in modified LDL uptake.